Characterization of the milk processing and processing industry: Case study in a dairy - Oliveira, Antonia Valcemira (Pubvet, 2020)
Agribusiness is extremely important in the world economy. In Brazil, it is one of the most relevant sectors contributing to the Gross Domestic Product - GDP. However, dairy industries have challenges that must be overcome to leverage production, as consumption of milk and dairy products is steadily increasing. In this sense, the objective was to conduct a survey and systematize a set of primary information about the processing and industrial processing sector of milk in Milk Dairy Honey in the municipality of Sena Madureira-AC, Brazil. The method adopted was a descriptive, investigative and exploratory methodological approach, through qualitative and quantitative analysis. Data were collected through interviews and a questionnaire to identify the company's history, production destination, production potential, market prospects, company characterization; characterization of productive units; process control in manufacturing; employed labor and environmental control (waste). The information obtained was tabulated and analyzed with the aid of Excel software (Microsoft office 2013). Through the data analyzed it was found that the production process occurs following the production steps: reception, pasteurization, manufacturing and packaging. The company receives fresh milk from 26 producers for the production of pasteurized milk, cheese, butter and yogurt. Milk production in 2016, 2017 and 2018 were: 342,068, 387,435 and 389,116 liters, respectively. In 2018, an average of 32,426 liters of milk per month was benefited. The production of pasteurized milk in 2018 was 292,134 liters, cheese 82,813 kg, yogurt 8,810 units and butter 1,155 kg. They are sold in local shops (supermarkets and bakeries) and delivered to municipal schools for school meals. It can be concluded that Laticínio Leite Mel has a fundamental role for the development of the municipality of Sena Madureira-AC, generating employment and income to the local community, fixing the farmers in the rural area, as it contributes significantly to the local social and economic development.
Keywords: agribusiness; milk supply chain; dairy products; economic development; production